PENGARUH REPUTASI PERUSAHAAN, TRUST DAN WEBSITE QUALITY TERHADAP LOYALITAS PELANGGAN ONLINE SHOP OLX.COM STUDI KASUS PADA MAHASISWA FAKULTAS EKONOMI ANGKATAN TAHUN 2015 UNIVERSITAS ISLAM MALANG - Gusti Suta Pahlopi; Rois Arifin (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTThis study aims to explain the influence of corporate reputation, trustand website quality to the loyalty of online shop customers olx.com, StudentFaculty of Economics class year 2015 UNISMA. The population of this researchis all students of faculty of economics year 2015 UNISMA. The sample was takenby using purposive sampling method so that 88 respondents who fulfill thecondition as sample. This research uses primary data and multiple regressionanalysis method.The result of this research show that firm reputation variable havepositive and significant influence to customer loyalty, trust variable have positiveeffect and not significant to customer loyalty, website quality variable havepositive and insignificant to customer loyalty, simultaneously variable of companyreputation, trust and website quality have significant influence .Keywords: company reputation, trust, website quality, customer loyalty.